(untitled) (International Journal of Advanced Research in Computer Science, 2017)
WSN is a collection of very tiny nodes which has gained a high attention of the researchers due to its various applications in different sectors. The tiny devices, called the sensor nodes are deployed in a harsh area and left unattended to continuously report the parameters of the environment, based on the application. The tiny nodes are constrained by the energy and hence it becomes necessary to consume less energy by using the means of clustering so that the lifetime of the whole network can be prolonged. This paper will represent an introduction to the clustering and various issues regarding to it. Keywords: WSN, Sensor Node, Energy Efficiency, Clustering Algorithm